Historische Gärten Österreichs / Bd. 3 Garten und Parkanlagen von der Renaissance bis um 1930 - Berger, Eva (2004)
In the year 1999 the project of the inventarisation of the historic gardens in Austria, financed by the Austrian Science Fund FWF was finished with the manuscript "Historic Gardens in Austria. Gardens and Parks from the Renaissance to 1930". Since 1984 this project was in charge of the author with some other co-workers at the Technical University of Vienna, Department of Landscape Planning and Garden History. This first Austrian inventory tended to consider public and private gardens, parks and artistically formed landscapes of all nine Austrian states from the Renaissance to about 1930 in a systematic manner. In the years of the inventarisation over 1750 historic gardens and parks were discovered, photographed and described. For the publication this numerous and mostly unknown quantity of gardens and parks was arranged in typological groups: gardens and parks of ecclesiastic dwelling-houses as monasteries, convents and cloisters, episcopal and provost buildings, parsonages, gardens and parks of profane buildings as castles, chateaus, palaces, manor-houses, country-houses, villas, dwelling-buildings, development houses, farmhouses, mills, factories, public buildings (monumental buildings) of culture (museum, theatre), education (school, university, botanic garden, arboretum), healing and welfare work (hospital, sanatorium, old people´s home, residential home, youth welfare home), administration (office, embassy), catering and hotel industry and tourism ( hotel, inn, restaurant), sport, recreation and leisure ( swimming-bath, shooting-stand, amusement park, leisure centre), public gardens and parks (without any main-building) as green places, village parks, town parks, village woods, town woods, parks of a spa, memorial parks, promenades, green outside staircases. With the elaboration of the results of the inventarisation, with the consideration of the trade literature, historic maps, plans, views, pictures and other source materials it was possible to present the first documentation of the existing historic gardens and parks in Austria in three volumes, published 2002-2004 (Böhlau Verlag, Wien-Köln-Weimar). This first survey makes known the rich existence of historic garden substance, is available to further scientific research on Austrian garden art and garden culture and affords first informations to protect and preserve this important cultural heritage. The third volume of the inventarisation of the historic gardens and parks in Austria presents the public and private gardens of the Austrian capital Vienna This first survey makes known the rich existence of historic gardens substance, is available to further scientific research on Austrian garden art and garden culture and affords first informations to protect and preserve this important cultural heritage.